An Exploration of correctional counselor workloads in a Midwestern state - Matz, Adam K. (The prison journal, 2020)
Time studies have been conducted across a variety of occupations. However, no known research has examined the workload of correctional counselors. In this study, the Iowa Department of Corrections, in partnership with the American Probation and Parole Association, performed a workload evaluation of over 100 correctional counselors who participated in a time study. The most common activities concerned inmate requests, classification, assessment, release planning, treatment group work, and administrative tasks. Most concerning, respondents indicated anywhere from 20% to 50% of the activities engaged in were unsatisfactorily completed.